Stunting Pemahaman Orang Tua Tentang Kebutuhan Gizi Dalam Mengurangi Risiko Balita Stunting Di Desa Mendalan - Wardah, Zahrotul; Triwanto, Rio Bayu; Amalia, Rizky Ardina; Fitriyah, Liza Nurmaya Indi; Hidayat, Rifqi Thariq; Andyarini, Esti Novi (Journal of Health Science and Prevention, 2025)
Stunting is a condition of growth failure in children under five years of age caused by long-term malnutrition and can be recognized by abnormal height for their age. This condition has significant implications for a child's overall health and development, potentially leading to long-lasting physical and cognitive impairments. Addressing the root causes of stunting is crucial for improving children's well-being and ensuring they reach their full potential. The causes of stunting are not only related to socioeconomic conditions and maternal nutrition but can also be influenced by parents' occupation, parenting styles, and exclusive breastfeeding. The purpose of this study is to determine the level of parental understanding of balanced nutrition and to review the role of education as one of the causes of the high stunting rate in Mendalan Village. Using a qualitative research method with a cross-sectional approach, data was collected through interviews and questionnaires administered to 55 pregnant women and mothers with stunted children. Based on the data obtained, one of the factors influencing understanding of balanced nutrition is education. Specifically, respondents in Mendalan Village have a low level of education, with only elementary (SD) and junior high school (SMP) graduates. Thus, the causal relationship between low education levels and parents' understanding of balanced nutrition influences the high risk of child stunting. This phenomenon can then be prevented by providing education on mental, physical, financial, and mindset readiness before becoming a parent.